S41 Utilisation of a respiratory non-malignant palliative care MDT. (12th November 2019) - Henderson, WI; Cameron, E; Cross, M; Embley, M; Lee, C; Morrison, D; Newman, W; Spears, M; Wilczynska, M; Wood, FT
Abstract : Introduction: Palliative care support is often more limited for patients with non-malignant respiratory conditions, despite their mortality and symptom burden being comparable to patients with cancer 1 . Having established a monthly non-malignant palliative care MDT within our department in 2013, we wanted to ascertain the characteristics of patients discussed at this meeting, as well as outcomes in terms of survival and place of death. We also wanted to assess how well anticipatory care plans were being communicated for these patients using the Key Information Summary (KIS). Methods: Administration staff provided lists of patients discussed between October 2013 and October 2018. Clinical Portal was used to collect demographic and outcome data. We assessed completion of the KIS in a smaller group of patients discussed between January 2017 and October 2018. Results: 66.7% of the patients (104/156) had COPD, the majority of the rest (47) had interstitial lung disease. ILD patients were on average older (median age 78 vs 70) and accounted for far fewer admissions in the year prior to MDT discussion (47 vs 322). A small number of patients were admitted multiple times, some being admitted as many as 19 times. 105 patients in total had a place of death documented, of these 65 (approximately 62%) died in hospital. The median survival for both groups was less than 1 year post MDT discussion although greater in the COPD group (216.5 vs 152.5 days). The KIS summary was completed for 31 of the 44 patients, however only 11 had an explicit decision regarding escalation to critical care documented. Discussion: Our data identifies a group of patients that were admitted to hospital multiple times prior to MDT. These patients in our experience suffer immense psychosocial upheaval and would benefit from more targeted palliative care support. We propose that protocols are put in place to identify these patients and trigger an automatic consideration of palliative care needs, including referral to specialist services where required. Reference: Bloom, Slaich, Morales, et al . Low uptake of palliative care for COPD patients within primary care in the UK. Eur Respir J 2018; 51:1701879